A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 2 PEKANBARU IN SUPPLYING CORRECT PRONOUNS - Dika Faradilla Wulandari; Effendy Gultom; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to find out the ability of the second year students of SMAN 2 Pekanbaru in supplying correct pronouns. The number of population is 260 who are divided into seven classes, they are XI IPA 1, XI IPA 2, XI IPA 3, XI IPA 4, XI IPS 1, XI IPS 2 and XI IPS3. The researcher uses cluster random sampling technique to determine the sample. The samples are 36 students from XI IPA 3. The needed data are taken from the students’ scores in supplying correct pronoun. The test contains 40 questions from four different pronouns, they are personal pronouns, possessive pronouns, reflexive pronouns, and possessive adjectives. The time allocation is 60 minutes. The result of the study shows that the ability of the second year students of SMAN 2 Pekanbaru in supplying correct pronouns is in good level with the mean score is 70.07. The highest mean score (72.22) is in supplying possessive pronouns. The lowest mean score (66.67) is in supplying reflexive pronouns.Key Words: Study, ability, supplying, pronouns